(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Uniform though a prisoner has the right to request, condemning is often seen as the most significant and last stage of the criminal justice system. It has the psychological impact of bringing justice to a satisfactory conclusion. However, the fact that in our country, the assessment of suitable punishment is based mostly on imprecise phrases such as aggravating or mitigating conditions or severity do not serve the aim of criminal justice administration. It’s considered ambiguous because what one judge finds aggravating or extenuating need not/will not be the same for another. Few Committee Reports have proposed the laying of systematic guidelines to solve this problem. The purpose of this article is to highlight the current method for determining appropriate punishment, as well as the necessity for organized sentencing guidelines based on judicial precedents and Committee Reports. The study concludes that, in order to avoid this disparity in sentencing, the judiciary must establish a clear set of guidelines for sentencing policies, as well as “ For particular actions that do not need the ultimate sentence but do necessitate a more serious sentence, life incarceration with repentance or release.